Analysis Clustering of the Global Pandemic Covid-19 using K-Means Algorithm - Bakti Siregar; Yosia (PT FORMOSA CENDEKIA GLOBAL, 2023)
A pandemic such as Covid-19 is one of the biggest real problems ever in the world. This case has confirmed how uncertainty affects the global economy. The pandemic Covid-19 cannot be solved by one method over the world, it depends on the severity of the case. Therefore, this research aims to cluster the severity of Covid-19 using the K-means algorithm to reflect the global economic conditions using data sources from